Helping yourself help others : a book for caregivers - CARTER, Rosalynn; Golant, Susan K. (New York : Times Books, 1994)
A personal account by Rosalyn Carter of her own caregiving experience while offering practical solutions for caregiving difficulties and includes information on home care services, nursing homes, and more.
Includes bibliographical references (pages 266-270) and index.
Keywords: Home care services; Chronically ill -- Home care; Chronically ill -- Family relationships; Home Nursing; Chronic Disease -- psychology; Family; Popular Works